2008
DOI: 10.1007/s10596-008-9116-8
|View full text |Cite
|
Sign up to set email alerts
|

The kriging update equations and their application to the selection of neighboring data

Abstract: A key problem in the application of kriging is the definition of a local neighborhood in which to search for the most relevant data. A usual practice consists in selecting data close to the location targeted for prediction and, at the same time, distributed as uniformly as possible around this location, in order to discard data conveying redundant information. This approach may however not be optimal, insofar as it does not account for the data spatial correlation. To improve the kriging neighborhood definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 18 publications
(21 reference statements)
0
63
0
Order By: Relevance
“…The simplest version of such a scheme would be via nearest neighbors (NN): X n (x) comprised of closest elements of X N to x. Emory (2009) showed that this works well for many common choices of K θ . However, NN designs are known to be sub-optimal (Vecchia 1988;Stein, Chi, and Welty 2004) as it pays to have some spread in X n (x) in order to obtain good estimates of correlation hyperparameters like θ.…”
Section: Local Approximate Gaussian Process Modelsmentioning
confidence: 99%
“…The simplest version of such a scheme would be via nearest neighbors (NN): X n (x) comprised of closest elements of X N to x. Emory (2009) showed that this works well for many common choices of K θ . However, NN designs are known to be sub-optimal (Vecchia 1988;Stein, Chi, and Welty 2004) as it pays to have some spread in X n (x) in order to obtain good estimates of correlation hyperparameters like θ.…”
Section: Local Approximate Gaussian Process Modelsmentioning
confidence: 99%
“…Now, using the kriging update formula (see, e.g., Barnes and Watson (1992); Gao et al (1996);Emery (2009), as well as Chevalier et al (2013a)), we obtain:…”
Section: Of the Centered Bivariate Gaussian With Covariance Matrixmentioning
confidence: 99%
“…, Z(x n+q )) = Z(X q ). One of the key ingredient to obtain the formulas and set up the algorithm happens to be the batch-sequential kriging update formulas of Emery (2009);Chevalier et al (2014), as detailed next. The paper is organized as follows: in Sect.…”
Section: Introductionmentioning
confidence: 99%